Lichens of fruit trees in the selected locations in Podlaskie Voivodeship [North-Eastern Poland] - Matwiejuk Anna (Environmental Protection and Natural Resources, 2017)
The aim of this paper is to present the diversity of the lichen species on fruit trees (Malus sp., Pyrus sp., Prunus sp. and Cerasus sp.) growing in orchards in selected villages and towns in the Podlaskie Voivodeship. Fifty-six species of lichens were found. These were dominated by common lichens found on the bark of trees growing in built-up areas with prevailing heliophilous and nitrophilous species of the genera Physcia and Phaeophyscia. A richer lichen biota is characteristic of apple trees (52 species) and pear trees (36). Lichens of the apple trees constitute 78% of the biota of this phorophyte growing in the fruit orchards in Poland. Of the recorded species, only two (Ramalina farinacea, Usnea hirta) are covered by partial protection in Poland.